Maternal Antenatal Treatments Influence Initial Oral Microbial Acquisition in Preterm Infants - Hendricks-Muñoz, Karen D.; Perez-Perez, Guillermo; Xu, Jie; Kim, Yang; Louie, Moi (American Journal of Perinatology, 2013)
Objective The purpose of this study was to analyze the association of maternal antenatal therapy on initial preterm infant oral microbial acquisition of gut metabolically important bacteria: Firmicutes, Bacteroidetes, Lactobacillus, Bifidobacterium, and Bacteroides species.Study Design Infant oral samples were collected prefeeding at 24 hours and analyzed using group-specific primers by real-time 16S rRNA quantitative polymerase chain reaction with analysis of variance and logistic regression to evaluate effect of antenatal exposure.Results Sixty-five infants <34 weeks' gestational age (GA) were evaluated; mean GA was 28.6 ± 2.6 (standard deviation) weeks. Infants unexposed to antenatal treatment (n = 5) acquired <1% Firmicutes, which was composed of 100% Lactobacillus species with no detectable Bifidobacterium, Bacteroidetes, or Bacteroides species. Infants exposed to antibiotics (n = 7), acquired fivefold less total bacterial density (TBD) with 45% Firmicutes 1.3% Lactobacillus species, 23.5% Bacteroidetes and rare Bacteroides. Compared with unexposed infants, steroids (n = 26) or steroid and antibiotics (n = 27) exposure led to an eightfold increase in TBD with <1% Lactobacillus species and Bacteroides species 100% and 30%, respectively (p < 0.04). Bifidobacterium was undetectable in all groups.Conclusion Preterm infant exposure to routine maternal antenatal treatments influence early oral microbial acquisition during the primary hours related to establishment of gut commensal bacteria.
Keywords: antenatal therapy; preterm infant; oral microbiota; Lactobacillus